Porträtt av greve Johan Fredrik Aminoff f. 1756, d.1842. - Cardon, Johan Elias (1802-1878), litograf
Porträtt av greve Johan Fredrik Aminoff f. 1756, d.1842.
Keywords: porträtt; grevar; officerare; kanslerer; rilax